Realisasi Corporate Social Responsibility sebagai Perwujudan Pilar Program Tanggung Jawab Sosial dan Lingkungan : Studi Kasus PT Pelabuhan Indonesia Sub Regional Bali Nusra - Ni Km. Silvia Darmaningrum; Ni Putu Karnhura Wetarani (LPPM Institut Pendidikan Nusantara Global, 2026)
Corporate Social Responsibility (CSR) is an instrument that bridges business interests with corporate social obligations, which will actually represent a company's impact on the economic, environmental, and social sectors in which the company operates. Running in line with regulations, 4% of the net profit of BUMN will be required to be allocated as CSR funds, which are then called Social and Environmental Responsibility (TJSL). Often the effectiveness of its distribution is called only ceremonial and the location of the target is questioned. This study aims to examine the application of implementation and strategy at PT Pelabuhan Indonesia Sub Regional Bali Nusra with reference to the four pillars of the TJSL program. Through the application of qualitative research methods, a case study approach at PT Pelabuhan Indonesia Sub Regional Bali Nusra with reference to the concept of CSR implementation and alignment of the Triple Bottom Line. This study results that the realization of Corporate Social Responsibility at PT Pelabuhan Indonesia Sub Regional Bali Nusra has demonstrated efforts to transform and balance between ceremonial assistance and sustainable community empowerment programs through the four pillars of the TJSL program. This realization requires a company commitment to create stability between community needs and build shared interests of stakeholders. And efforts to optimize program monitoring are needed to cover quality control gaps in the field in order to build a reporting stage that has implications for sustainability. eroperasi. Berjalan slaras dengan peraturan atas 4% dari laba bersih perusahaan BUMN akan wajib dialokasikan sebagai dana CSR yang kemudian disebut Tanggung Jawab Sosial dan Lingkungan (TJSL). Seringkali efektivitas penyalurannya diserukan hanya bersifat seremonial dan dipertanyakan letak kemerataan sasarannya. Penelitian ini bertujuan untuk menelaah aplikasi atas implementasi dan strategi pada PT Pelabuhan Indonesia Sub Regional Bali Nusra dengan acuan empat pilar program TJSL. Melalui penerapan metode penelitian kualitatif pendekatan studi kasus PT Pelabuhan Indonesia Sub Regional Bali Nusra dengan mengacu pada konsep implementasi CSR dan penyelarasan Triple Bottom Line. Penelitian ini menghasilkan bahwa realisasi Corporate Social Responsibility PT Pelabuhan Indonesia Sub Regional Bali Nusra telah menunjukkan upaya transformasi dan penyeimbangan antara bantuan bersifat seremonial dengan program pemberdayaan masyarakat yang berkelanjutan melalui empat pilar program TJSL. Realisasi tersebut diperlukan komitmen perusahaan untuk menciptakan kestabilan antara kebutuhan masyarakat dan membangun kepentingan bersama pemangku kepentingan (stakeholders). Serta upaya mengoptimalkan monitoring program diperlukan untuk menutupi celah kontrol kualitas di lapangan guna membangun tahap pelaporan yang berimplikasi pada keberlanjutan.